Comparison of Magnetic Resonance Imaging Features Between Programmed Cell Death 1/Programmed Cell Death Ligand 1 Inhibitor-Induced Hypopituitarism and Idiopathic Hypopituitarism in Japanese Subjects - Iwamoto, Yuichiro; Kimura, Tomohiko; Dan, Kazunori; Iwamoto, Hideyuki; Sanada, Junpei; Fushimi, Yoshiro; Katakura, Yukino; Shimoda, Masashi; Nakanishi, Shuhei; Mune, Tomoatsu; Kaku, Kohei; Kaneto, Hideaki (Curēus (Palo Alto, CA), 2024)
Objective Immune checkpoint inhibitor-associated hypopituitarism (ICI-HP) is a rare immune-related adverse event (irAE) of ICIs. This study aimed to identify characteristic pituitary findings on magnetic resonance imaging (MRI) in ICI-HP. Methods This study is a single-center, retrospective, observational study. Among 95 patients admitted to our hospital for examination of hypopituitarism between January 2010 and December 2022, 26 patients with normal pituitary function (NPF), 13 patients with ICI-HP, and 13 patients with idiopathic hypopituitarism (IHP) were included and analyzed. Results For participants with ICI-HP, the time from ICI administration to ICI-HP diagnosis was 125 (56-212) days. Compared to the NPF, participants in the ICI-HP and IHP were significantly older (p<0.01) - the highest number of patients presented with isolated adrenocorticotropic hormone deficiency in both ICI-HP and IHP. Pituitary volume was not significantly different among the three groups (p=0.68). The width of the pituitary stalk was 1.8 (1.5-2.0) mm in NPF and 1.8 (1.7-2.2) mm in IHP, whereas it was 2.4 (2.4-2.7) mm in ICI-HP and was significantly larger compared to the other groups (p<0.01). Conclusion This study identified no pituitary enlargement in ICI-HP compared to NPF or IHP. However, the pituitary stalk was significantly thickened in ICI-HP compared to the other groups. Pituitary stalk enlargement may be a characteristic MRI finding of ICI-HP.